Utilization of Wavewatch III Model Output Data for High Wave Analysis - Ricky Daniel Aror; Wilhelmina Patty; Andri Ramdhani (Marine Science Department Diponegoro University, 2019)
This study discusses the occurrence of extreme waves in North Sulawesi waters from 17 to 24 June 2016 using Wavewatch III (WW3) model output data with resolution 0.125o x 0.125o extracted from MIDAS-BMKG. The extracted WW3 data is mapped using ArcMap and presented in graphical form. Based on the results of the study, the significant wave height is in the range of 0.0 to 1.0 m and the average wind speed ranges from 0 to 15 knots in the early phase of 17-19 June 2016. Significant wave increases in the peak phase of 20-22 June 2016 that reaches 1.5 - 2.0 m and average wind speeds reach 25 knots. The average wind speed and the significant wave height decreased after June 23, 2016. The high of the significant wave are influenced by the low-pressure circulation in the atmosphere near the Sangihe-Talaud Islands. Further study can be done as a comparison of this study e.g. using wave data from altimeter satellites or comparing with other parameters such as the influence of swell and wind sea.